Infectious CNS disease as a differential diagnosis in systemic rheumatic diseases: three case reports and a review of the literature. Issue 1 (1st January 2003) - Warnatz, K; Peter, H H; Schumacher, M; Wiese, L; Prasse, A; Petschner, F; Vaith, P; Volk, B; Weiner, S M
Abstract : Background: Immunosuppressive treatment of rheumatic diseases may be associated with several opportunistic infections of the brain. The differentiation between primary central nervous system (CNS) involvement and CNS infection may be difficult, leading to delayed diagnosis. Objective: To differentiate between CNS involvement and CNS infection in systemic rheumatic diseases. Methods and results: Three patients with either longstanding or suspected systemic rheumatic diseases (systemic lupus erythematodes, Wegener's granulomatosis, and cerebral vasculitis) who presented with various neuropsychiatric symptoms are described. All three patients were pretreated with different immunosuppressive drugs (leflunomide, methotrexate, cyclophosphamide) in combination with corticosteroids. Magnetic resonance imaging of the brain was suggestive of infectious disease, which was confirmed by cerebrospinal fluid analysis or stereotactic brain biopsy (progressive multifocal leucoencephalopathy (PML) in two and nocardiosis in one patient). Discussion: More than 20 cases of PML or cerebral nocardiosis in patients receiving corticosteroids and cytotoxic drugs for rheumatic disease have been reported. The clinical aspects of opportunistic CNS infections and the role of brain imaging, cerebrospinal fluid analysis and stereotactic brain biopsy in the differential diagnosis are reviewed.